1981
DOI: 10.1113/jphysiol.1981.sp013976
|View full text |Cite
|
Sign up to set email alerts
|

Membrane properties of solitary horizontal cells isolated from goldfish retina.

Abstract: 6. The steady-state current-voltage (I-V) curve, measured by applying constant current pulses, was S-shaped (current on the abscissa) and composed of inward-and outward-going rectifying regions and a transitional region between them. A similar non-linear I-V relationship has been reported in vivo.7. The transitional region was characterized by a sudden potential jump and hysteresis, suggesting the presence of a 'negative resistance'. This potential jump appeared not to be produced by the Ca-conductance mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 62 publications
7
86
0
Order By: Relevance
“…It is possible that the prolonged depolarization may also arise from a calcium-dependent current, since very long duration regenerative potentials in other neurones have been shown to be calcium dependent (Tachibana, 1981;Ishizuka, Hattori & Akaike 1984;Murakami & Takahashi, 1987) and it is known that two classes of regenerative calcium action potentials can co-exist in some cells (Miller, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the prolonged depolarization may also arise from a calcium-dependent current, since very long duration regenerative potentials in other neurones have been shown to be calcium dependent (Tachibana, 1981;Ishizuka, Hattori & Akaike 1984;Murakami & Takahashi, 1987) and it is known that two classes of regenerative calcium action potentials can co-exist in some cells (Miller, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The resting potentials of the cells described in the present study (-59 + 6 mV, mean + S.D., n = 109) were determined after withdrawing the electrode from each cell studied, and agreed well with values reported previously (cf. Tachibana, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Retinas of adult common goldfish (Caramsius auratus), each approximately 10 cm in body length, were dissociated into single cells by techniques described in detail elsewhere (Tachibana, 1981 The solitary horizontal cells described in the present report were identified by their morphological appearance, and by the wave form of their current-pulse-triggered action potentials (cf. Tachibana.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the HCs isolated from goldfish retina show nonlinear properties which can be attributed to voltage-gated K ÷ and Ca ~+ channels (Tachibana, 1981(Tachibana, , 1983). We did not include voltage-gated channels in our model since these channels are normally not seen in an isolated retina.…”
Section: Voltage-gated Channelsmentioning
confidence: 99%
“…For simplicity we will refer to these channels as glutamate-modulated Na + channels. Although various voltage-dependent channels are present in goldfish HCs (Tachibana, 1981(Tachibana, , 1983), we did not include these voltage-dependent nonlinearities in the model. R-, G-, and B-cones modulate separate Na + channels in the HC membrane, and therefore interact nonlinearly (Kamermans et al, 1989a).…”
Section: Rmentioning
confidence: 99%